The Implementation of Chatgpt in English Language Learning in the Philippines And Indonesia - Djuwari, Djuwari; Pila, Rowena A.; Syaikhon, Mochammad (LP. Ma'arif Janggan Magetan, 2025)
ChatGPT has gained popularity in research writing and language teaching, yet its specific influence on students’ English learning processes remains underexplored. This study aims to investigate students’ experiences using ChatGPT in English language learning from two countries: the Philippines and Indonesia. Employing a qualitative research design, the study purposively collected the data from 90 university students—50 from University Technology in the Philippines and 40 from Universitas Nahdlatul Ulama Surabaya (UNUSA), Indonesia. They completed questionnaires via Google Forms, using a five-point Likert scale (strongly agree to strongly disagree) to express their perceptions of ChatGPT’s role in their learning. In addition, interviews were conducted with four teachers (two from each institution) to deepen insights into classroom impacts. Findings reveal that ChatGPT significantly enhances students’ English learning by boosting creativity, encouraging critical thinking, improving engagement, and supporting knowledge retention. It also aids in time management, facilitates collaborative problem-solving, and optimizes learning resources. Teachers reported 13 distinct positive effects on student learning outcomes. Therefore, ChatGPT is a valuable educational tool that transforms traditional learning environments and better prepares students with essential 21st-century skills. It is recommended that ChatGPT be more widely integrated into English language instruction to maximize its benefits.